2020
DOI: 10.1111/apa.15453
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review showed that low and moderate prenatal alcohol and nicotine exposure affected early child development

Abstract: From the time of fertilisation, human offspring are sensitive to environmental factors. 1,2 Toxic substances are the most influential factors for the development of the unborn child, 3 and alcohol and nicotine are increasingly being consumed during pregnancy. 3,4 Both substances pass directly through the placenta into the foetal blood circulation, causing toxic effects, for example on cell development. 4 In addition, the biochemically immature organism delays detoxification processes. 5 Hence, prenatal exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
(165 reference statements)
0
12
0
Order By: Relevance
“…Prenatal alcohol exposure is a risk factor for children's cognitive development [128]. In contrast, a systematic literature review examined 27 cohort studies (published 2007-2018) [129].…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…Prenatal alcohol exposure is a risk factor for children's cognitive development [128]. In contrast, a systematic literature review examined 27 cohort studies (published 2007-2018) [129].…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…The result is functional deficits, especially impairment of executive and motivational functions [46]. Prenatal alcohol exposure may hamper the children's cognitive development [47]. Physical exercise: Physical exercise helps retard cognition decline [48].…”
Section: Discussionmentioning
confidence: 99%
“… 18 Human research has provided limited evidence that low to moderate PAE is detrimental to the offspring, with a recent systematic review reporting adverse effects on early child development in six studies, no effect in five studies, and a weak positive effect in two. 19 The authors concluded that conflicting findings following low PAE may in part be due to a lack of sensitivity for detecting some outcome measures, and inadequate accounting for confounding, environmental and social factors. Since this review was published, a secondary analysis of 9719 children from the Adolescent Brain Cognitive Development Study found that even children with low PAE demonstrated poorer psychological and behavioural outcomes at around 9–10 years of age.…”
Section: Introductionmentioning
confidence: 99%